From hydrology to hydroarchaeology in the ancient Mediterranean - Polizzi, Giovanni,; Ollivier, Vincent,; Bouffier, Sophie, (Archaeopress Archaeology, 2022)
This volume is devoted to the study of water management in ancient cities. It compares the approaches and methods adopted by researchers from different disciplinary sectors to identify the water conditions of past societies and to highlight the measures they have taken to adapt to their water resources.